Knowledge and Behavior of Patients with Diabetes Mellitus Type II toward of Diabetic Foot Care at Endocrinology and Diabetes Center in AL-Samawa City, Iraq - Mezher, Mohammed K.; Abed, Rajaa Ibrahim (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to detect the outcome of the instructional program's effectiveness in the knowledge and behavior of patients with diabetes type 2 regard to diabetic foot care. A quasi-experimental study to determine the effectiveness of the counseling program on the patient's knowledge and behavior towards diabetic foot care, the study was conducted at the Center for Endocrinology and Diabetes in the city of Samawah from (October 2019 to May 2020), A non- Probability (purposive Sample) of (30) patients with diabetes Type 2 selected. The results of the study showed that the majority of respondents were between (54-60 years), about (26.7%), about half of the respondents are (either they do not read or write or read and write only) and (66.7 - 70%) live in rural areas, and about (70%) of them have less than (300,000) Iraqi dinars for monthly income. The majority do not receive information about foot care. Also, most of the participants had poor knowledge and behavior towards the foot care of the pre-test, which improved after the application of the program (post-test). The study recommended conducting a new survey for diabetics in the city of Samawah and issuing a booklet on patient behaviors related to foot care and distributing it to patients during their visit to health institutions, providing the Center for Diabetes and Endocrinology in the city of Samawah with professional nurses from nursing colleges to provide periodic lectures to patients on diabetic foot care